Breeding phenology, reproductive traits and apparent survival of sympatric Marsh Warbler Acrocephalus palustris and Blyth's Reed Warbler Acrocephalus dumetorum. Issue 2 (3rd April 2018) - Shitikov, Dmitry; Knyazeva, Irina; Grabovsky, Alexander
ABSTRACT: Capsule: Sympatric Marsh Warblers Acrocephalus palustris and Blyth's Reed Warblers Acrocephalus dumetorum differ significantly in their life history traits. Aims : To provide a direct comparison of demographic parameters among two sympatric populations of the closely related Marsh Warbler and Blyth's Reed Warbler. Methods : We examined breeding phenology and reproductive traits at a 25 ha study plot. We use program MARK to estimate daily nest survival and adult apparent survival rates. Results : On average, Marsh Warblers laid the first eggs 3 days later than Blyth's Reed Warblers. Mean clutch size in the Marsh Warbler was significantly lower than in the Blyth's Reed Warbler. There are no significant differences between the two species for nest daily survival, duration of incubation and nestling periods. Apparent survival of adults was slightly higher in Marsh Warblers than in Blyth's Reed Warblers. Conclusion : Our findings suggest that two ecologically similar sympatric species differ significantly in terms of life history traits. We assume that observed differences could be the result of adaptations to environmental factors in the central parts of the species' ranges or due to differences in mortality on migratory pathways or wintering grounds.